Optimizing Inventory Management To Address Delivery Delays And Cost Inefficiencies: A Case Study Of Pt Genta Trikarya - Sabiq, Alwan Hilmi (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study examines how inventory management can help reduce delivery delays and cost inefficiencies in the musical instrument manufacturing industry, focusing on PT Genta Trikarya. Managing the right amount of stock is essential to avoid shortages that slow down production and excess inventory that increases storage costs. To solve this, the Economic Order Quantity (EOQ) method is used to determine the best order size, and the Reorder Point (ROP) method helps decide when to restock materials. These strategies ensure that inventory levels stay balanced, costs are minimized, and deliveries are on time. The study also uses Total Inventory Cost Analysis to measure cost savings and Demand Forecasting to predict future stock needs. The results show that EOQ reduces total inventory costs from IDR 107,194,708 to IDR 34,928,610, while lowering the number of orders from 45 to 9 per year, improving cost efficiency. However, challenges like manual inventory tracking, outdated technology, and unreliable suppliers still affect performance. The study suggests solutions such as automated inventory tracking, ERP systems, and stronger supplier partnerships to improve efficiency. This research uses a mixed-method approach, combining numerical data analysis with business insights to understand the best inventory management strategies. The findings suggest that a data-driven inventory system can significantly lower costs, reduce stock problems, and improve supply chain performance, ensuring smoother operations in the musical instrument manufacturing industry.